THE BIOMECHANICAL STUDY ON FORCES AND MOMENTUM THAT ACT ON ANKLE JOINT WHEN STAMPING IN ATTACK AT VOLLEYBALL - Florian Benedek; Roxana Benedek; Mirela Benedek; Gougou Gramatopol (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Modern research has shown that not only the mechanic factor by itself can influence the structural modifications but it must also be assisted by the tissual biochemical factor which creates the conditions for the disappearance of some structures and the appearance of others.